Designing for Discovery and Re-Use: the ‘ANDS Data Sharing Verbs’ Approach to Service Decomposition - Adrian Burton; Andrew Treloar (International Journal of Digital Curation, 2009)
This paper describes how the Australian National Data Services (ANDS) is designing systems to support data sharing and Re-use. The paper commences with an overview of the setting for ANDS, before introducing ANDS itself. The paper then structures its discussion of ANDS services for Re-use in terms of the ANDS Data Sharing Verbs: Create, Store, Describe, Identify, Register, Discover, Access and Exploit. For each of the data verbs, a rationale for its importance is provided together with a description of how it is being implemented by ANDS. The paper concludes by arguing for the data verbs approach as a useful way to design and structure flexible services in a heterogenous environment.